India Financial Sector Assessment - World Bank; International Monetary Fund (World Bank, Washington, DC, 2017)
Against the backdrop of important structural reforms and terms of trade gains, India recorded strong growth in recent years in both economic activity and financial assets. Increased diversification, commercial orientation, and technology-driven inclusion have supported growth in the financial industry, backed by improved legal, regulatory, and supervisory frameworks. Yet, the financial sector is grappling with significant challenges, and growth has recently slowed. Highnonperforming assets (NPAs) and slow deleveraging and repair of corporate balance sheets are testing the resilience of the banking system and holding back investment and growth. The largest banks appear sufficiently capitalized and profitable to withstand a deterioration in economic conditions, reflecting relatively solid capital buffers and, particularly for the private banks, core profitability that is strong enough to cover credit costs. There is a group of public sector banks (PSBs) where vulnerabilities seem highest; these banks would require additional capital under the baseline scenario and some would almost deplete capital buffers due to growing NPAs and provisioning needs if stress intensifies. Capital needs are manageable in the aggregate, ranging between 0.75 percent of GDP in the baseline to 1.5 percent of GDP in the severe adverse scenario. Much needed efforts are now underway to accelerate the process of NPA resolution. The various debt restructuring schemes introduced over the past years have had limited uptake, and agreement among lenders has been hampered by their uneven capacity to withstand losses. The RBI was recently empowered to direct restructuring cases to the insolvency process, with the potential for insolvency used to exert pressure on creditors to finalize debt restructuring agreements outside the court process. This new approach shows promise of further progress, but more needs to be done to ensure that the debt restructuring process gains traction: banks need additional provisions and capital buffers; corporates need to undergo sustainable financial and operational restructuring; and infrastructure for debt restructuring needs to be improved.